2015
DOI: 10.1177/0098628315589505
|View full text |Cite
|
Sign up to set email alerts
|

The Scientific Status of Learning Styles Theories

Abstract: Theories of learning styles suggest that individuals think and learn best in different ways. These are not differences of ability but rather preferences for processing certain types of information or for processing information in certain types of way. If accurate, learning styles theories could have important implications for instruction because student achievement would be a product of the interaction of instruction and the student's style. There is reason to think that people view learning styles theories as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
179
1
17

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(198 citation statements)
references
References 23 publications
1
179
1
17
Order By: Relevance
“…The continued use of Learning Styles is, in theory, associated with a number of harms (Pashler et al, 2008; Riener and Willingham, 2010; Dekker et al, 2012; Rohrer and Pashler, 2012; Dandy and Bendersky, 2014; Willingham et al, 2015). These include a ‘pigeonholing’ of learners according to invalid criteria, for example a ‘visual learner’ may be dissuaded from pursuing subjects which do not appear to match their diagnosed Learning Style (e.g., learning music), and/or may become overconfident in their ability to master subjects perceived as matching their Learning Style.…”
Section: Introductionmentioning
confidence: 99%
“…The continued use of Learning Styles is, in theory, associated with a number of harms (Pashler et al, 2008; Riener and Willingham, 2010; Dekker et al, 2012; Rohrer and Pashler, 2012; Dandy and Bendersky, 2014; Willingham et al, 2015). These include a ‘pigeonholing’ of learners according to invalid criteria, for example a ‘visual learner’ may be dissuaded from pursuing subjects which do not appear to match their diagnosed Learning Style (e.g., learning music), and/or may become overconfident in their ability to master subjects perceived as matching their Learning Style.…”
Section: Introductionmentioning
confidence: 99%
“…It is rather striking that an overwhelming majority of professional educators strongly believe in the benefits of learning styles while other experts point out that there is no scientific support for this idea and call it a "neuromyth" (Dekker et al, 2012;Howard-Jones, 2014;Willingham et al, 2015;Hood et al, 2017). While the lack of evidence in support of the theory of learning styles remains a major issue in the field, the same lack of evidence makes it is hard to go against the intuitive attitude of this many educators.…”
Section: Discussionmentioning
confidence: 99%
“…It is also conceivable and that some learners would be more comfortable with one teaching style as compared to another. In support, extensive recent surveys have found that about 95% of teachers and educators with diverse backgrounds have agreed that indeed there are learning styles and that students learn better if instructed in their preferred style (Dekker et al, 2012;Howard-Jones, 2014;Willingham et al, 2015). Following this popularity, various educational institutions and companies advertise programs and inventories to address how to profile individual learning styles and how to accordingly improve teaching and learning practices.…”
Section: Pros and Cons To The Idea Of Learning Styles Prosmentioning
confidence: 99%
“…Entwhistle & Ramsden, 1982;Entwhistle, 2007) have recorded the complex and multi-facetted nature of the teaching-learning environment, as understood from a long tradition of scholarly investigation into how students learn. While there is a debate regarding the exact details of student learning, including a lively critique of the concepts and models of learning styles and of how students learn (Pashler et al, 2008;Rohrer & Pashler, 2012;Klitmøller, 2015;Willingham et al, 2015), in simple terms, as Darling-Hammond (1998) says in response to a question about what teachers need to know, "The audience is also key: A skilful teacher figures out what students know and believe about a topic and how learners are likely to "hook into" new ideas.". One of the defining characteristics of scholars of teaching and learning is their engagement with their partners in teaching and learning, the students.…”
Section: Introductionmentioning
confidence: 99%